Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1042/0264-6021:3580001
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of ATP secretion in the liver by therapeutic bile acids

Abstract: ATP receptors are ubiquitously expressed and are potential targets for the therapy of a number of disorders. However, delivery of ATP or other nucleotides to specific tissues is problematic, and no pharmacological means to stimulate the release of endogenous ATP has been described. We examined the effects of the bile acid ursodeoxycholic acid (UDCA) on ATP release into bile, since this bile acid is the only agent known to be of therapeutic benefit in secretory disorders of the liver, and since its mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Pathological conditions such as cell swelling result in release of ATP from both hepatocytes (28) and cholangiocytes (29). In addition, the therapeutic bile acids ursodeoxycholate and tauroursodeoxycholate induce hepatocytes to secrete ATP into bile (16). The current work establishes cAMP-induced, autocrine release of ATP from cholangiocytes as a physiological route by which ATP appears in bile.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Pathological conditions such as cell swelling result in release of ATP from both hepatocytes (28) and cholangiocytes (29). In addition, the therapeutic bile acids ursodeoxycholate and tauroursodeoxycholate induce hepatocytes to secrete ATP into bile (16). The current work establishes cAMP-induced, autocrine release of ATP from cholangiocytes as a physiological route by which ATP appears in bile.…”
Section: Discussionmentioning
confidence: 71%
“…Because cAMP-mediated secretion depends upon stimulation of apical P2Y receptors, agents that increase biliary ATP would be expected to stimulate ductular secretion. Ursodeoxycholate induces hepatocytes to secrete ATP and increases the concentration of ATP in bile (16), so it could be predicted on this basis that this bile acid would stimulate bile flow and bicarbonate secretion and would be of potential benefit in cholestasis. Indeed, these are precisely the properties this bile acid displays (44), although the mechanism by which ursodeoxycholate exhibits its therapeutic effect is controversial and may be multifactorial (45).…”
Section: Discussionmentioning
confidence: 99%
“…ATP is a partial agonist for P2Y 12 and may also act as a relatively low-affinity antagonist for this receptor (8). ATP is released in bile by both hepatocytes and cholangiocytes via unknown mechanisms, whereas biliary ADP is likely a product of degradation of ATP (11,32,33). We previously demonstrated that ATP, ATP-␥S, and ADP affect [Ca 2ϩ ] i signaling in rat cholangiocytes via P2Y 1 , P2Y 2 , and P2Y 4 purinergic receptors localized to the apical plasma membrane (14).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that bile contains ATP and ADP, which are considered extracellular signaling molecules affecting cholangiocyte functions via apically located P2Y purinergic receptors (11,14,15,32,33,43,45), we further hypothesized that some P2Y receptors are expressed in cholangiocyte cilia, providing a chemosensory function.…”
mentioning
confidence: 99%
“…Experimental model of TUDCA-induced stimulation of hepatocellular secretion. TUDCA, taken up into the hepatocyte by the Na ϩ -taurocholate cotransporting polypeptide (Ntcp), stimulates apical vesicular exocytosis and insertion of key canalicular transporters such as the conjugate export pump, Mrp2, and the bile salt export pump, Bsep, via Ca 2ϩ -and PKC␣-dependent mechanisms 15,17 or via activation of p38 MAPK and Ras-, Raf-, Erk-1/2-dependent mechanisms 24 33 Interestingly, anion exchanger 2 expression and bicarbonate secretion are impaired in patients with PBC and are up-regulated after treatment with UDCA. 34,35 Thus, stimulation of cholangiocellular HCO 3 Ϫ secretion may contribute to the anticholestatic effect of UDCA at least in certain biliary diseases in which HCO 3 Ϫ secretion is impaired.…”
Section: Stimulation Of Hepatobiliary Secretionmentioning
confidence: 99%